Food in Captivity: Experiences of Women in Indian Prisons. (January 2018) - Chatterjee, Debolina; Chatterjee, Suhita Chopra
This article demonstrates how prison food is controlled by the state through denying female prisoners' choices in food consumption and excluding them from active roles in cooking. Narratives of women in three prisons of India have been used to analyze their experiences with prison food. A majority of inmates perceived food as negatively affecting their health during imprisonment. Some were found to use it as a medium to recreate special identities for themselves, contesting the power of the prison. The study suggests the need for better articulation of the intricate relationship between power, health, and food in Indian prison settings.